2022
DOI: 10.3389/fnbot.2022.834952
|View full text |Cite
|
Sign up to set email alerts
|

Linking Multi-Layer Dynamical GCN With Style-Based Recalibration CNN for EEG-Based Emotion Recognition

Abstract: Electroencephalography (EEG)-based emotion computing has become one of the research hotspots of human-computer interaction (HCI). However, it is difficult to effectively learn the interactions between brain regions in emotional states by using traditional convolutional neural networks because there is information transmission between neurons, which constitutes the brain network structure. In this paper, we proposed a novel model combining graph convolutional network and convolutional neural network, namely MDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Lu et al performed target detection on video-induced EEG signals, extracted EEG spatio-temporal features with graph convolution, and improved the SRM to select features with larger contributions [ 26 ]. Bao et al added an SRM to a CNN to extract deep features and select features with high correlation with emotion and obtained improved results in a subject-depended experiment on the SEED dataset (95.08%) [ 27 ]. Therefore, the introduction of the SRM to adaptively recalibrate the intermediate features learned from sub-bands can incorporate them into the feature maps, thereby minimizing the loss of information and improving the feature extraction ability of the network [ 27 ].…”
Section: Related Workmentioning
confidence: 99%
“…Lu et al performed target detection on video-induced EEG signals, extracted EEG spatio-temporal features with graph convolution, and improved the SRM to select features with larger contributions [ 26 ]. Bao et al added an SRM to a CNN to extract deep features and select features with high correlation with emotion and obtained improved results in a subject-depended experiment on the SEED dataset (95.08%) [ 27 ]. Therefore, the introduction of the SRM to adaptively recalibrate the intermediate features learned from sub-bands can incorporate them into the feature maps, thereby minimizing the loss of information and improving the feature extraction ability of the network [ 27 ].…”
Section: Related Workmentioning
confidence: 99%
“…Despite most of the surveyed papers being relatively recent, a wide range of GNN-based methods has already been proposed to classify EEG signals in a diverse set of tasks, such as emotion recognition, brain-computer interfaces, and psychological and neurodegenerative disorders and diseases [46], [53], [54], [56], [58], [61], [70], [72], [75], [83], [89], [106] Chebyshev Graph Convolution ✗ ✓ ✗ [49], [51], [55], [57], [59], [66], [67], [69], [71], [74], [76]- [78], [80], [82], [85], [90], [97], [99], [104] Graph Attention Network ✓ ✗ ✗ [60], [62], [73], [84], [88], [94], [98] This survey categorises the proposed GNN models in terms of their inputs and modules. Specifically, these are brain graph structure, node features and their preprocessing, GCN layers, node pooling mechanisms, and formation of graph embeddings.…”
Section: Discussionmentioning
confidence: 99%
“…These methods can be generally categorised as learnable or pre-defined. Multiple/Combined graph definitions -- [47], [49], [53], [54], [57]- [59], [61]- [64], [67], [69], [72], [79], [79], [81], [82], [87], [92], [102] [51], [53], [55], [57], [71], [72], [75], [78], [81], [82], [87], [89], [90], [92], [93], [93], [95]- [99], [101], [102] Raw signal ✓ ✗ ✗…”
Section: Definition Of Brain Graph Structurementioning
confidence: 99%
“…Recently, EEG channel connectivity features have been widely used in ER, and several studies have demonstrated the effectiveness of connectivity features for ER. Among the functional connectivity, PCC, PLV, and MI were used frequently in the literature, such as PCC was used by the study [7], [8], [21], [23], [41], [43], [49], [51], [52], [56], [57], [58],…”
Section: Observations From the Existing Studies: Study Motivationmentioning
confidence: 99%
“…In the pre-processed version of the dataset, the EEG channels are ordered as listed in Table V. [7], [8], [21], [23], [41], [43], [56], [58], [49], [51], [52], [57] Functional non-linear (Phase-based measures) PLV [43] 2015 [7], [21], [23], [25], [58]- [64], [51] Functional non-linear (Information theoretic measures) MI [39] 2010 [24], [39], [42], [43], [46] NMI [45] 2019 [45], [56] Effective non-linear (Information theoretic measures) TE [7] 2020 [5], [7], [23], [51], [65], [66]…”
mentioning
confidence: 99%